The impact of depression on mothers' neural processing of their adolescents' affective behavior. Issue 8 (6th January 2022) - Barendse, Marjolein E A; Allen, Nicholas B; Sheeber, Lisa; Pfeifer, Jennifer H
Abstract: Depression affects neural processing of emotional stimuli and could, therefore, impact parent–child interactions. However, the neural processes with which mothers with depression process their adolescents' affective interpersonal signals and how this relates to mothers' parenting behavior are poorly understood. Mothers with and without depression ( N = 64 and N = 51, respectively; M age = 40 years) from low-income families completed an interaction task with their adolescents ( M age = 12.8 years), which was coded for both individuals' aggressive, dysphoric, positive and neutral affective behavior. While undergoing fMRI, mothers viewed video clips from this task of affective behavior from their own and an unfamiliar adolescent. Relative to non-depressed mothers, those with depression showed more aggressive and less positive affective behavior during the interaction task and more activation in the bilateral insula, superior temporal gyrus and striatum but less in the lateral prefrontal cortex while viewing aggressive and neutral affect. Findings were comparable for own and unfamiliar adolescents' affect. Heightened limbic, striatal and sensory responses were associated with more aggressive and dysphoric parenting behavior during the interactions, while reduced lateral prefrontal activation was associated with less positive parenting behavior. These results highlight the importance of depressed mothers' affective information processing for understanding mothers' behavior during interactions with their adolescents.